Amaurosis After Inferior Alveolar Nerve Block Injection in a Seven-year-old Girl: A Case Report and Review of the Literature - Arman Amirkhani; Hamid Mosleh (Tehran University of Medical Sciences, 2024)
A seven-year-old girl was referred for the treatment of her primary teeth. An inferior alveolar nerve block was administered using 1 mL of 2% lidocaine. Shortly after the injection, the patient experienced pain, erythema, blurred vision, and temporary loss of vision in her right eye. Based on these symptoms, a diagnosis of transient vision loss due to the anesthetic injection was made. The situation was explained to the child and her parents, assuring them that the complication was temporary. The right eye was covered with wet gauze, and all symptoms resolved within 20 minutes. A follow-up ophthalmological examination showed no abnormalities, and the procedure was successfully completed without further complications. A one-day follow-up revealed no issues.